**log**(1/10x) = -**log**(10x) = -**log**(10) -**log**(x) If logs are to base 10, this is: -(1 +**log**(x)).**log**(sqrt(xy^2)) =**log**(xy^2) / 2 = (**log**(x) + 2log(y) ) / 2 This may need modification if ...2 Answers · Science & Mathematics · 25/07/2007

**log**600 =**log**2*3*100 =**log**2 +**log**3 +**log**100 =**log**2 +**log**3 +**log**10^2 =**log**2 +**log**3 + 2**log**10 =**log**2 +**log**3 + 2 (1) = .301 + .477 + 2 = 2.7784 Answers · Science & Mathematics · 17/04/2010

**log**(M * T) =**log**(P) M * T = P Edit: Sorry for... let's assume that it was equal to zero: 3log(M) -**log**(T) + 2log(P) = 0 3log(M) + 2log(P) =**log**(...3 Answers · Science & Mathematics · 30/01/2012

**log**(base any) of x raised to the 3rd power is 3 times**log**(base any) x.**log**(base any) of x raised to the 1/2 power is 1/2...2 Answers · Science & Mathematics · 27/04/2007

I presume

**log**^7 means**log**[base 7]? Use the rules:**log**[base a] x +**log**[base a] y =**log**[base a] x·y**log**[base a] x -**log**[base a] y =**log**[base a] x/y Both**log**s in the first equation...3 Answers · Science & Mathematics · 07/04/2007

To solve logarithmic equation, these three

**log**properties are likely to come into play: 1)**log**[base b](ac) =**log**[base...base b](a) = c in exponential form is b^c = a Now, let's begin**log**(x + 54) -**log**(x + 2) = 2 -**log**(x) First, apply**log**property #2 to the left hand...12 Answers · Science & Mathematics · 23/12/2006

**log**_q (8q)=**log**_q(16*q/2)=**log**_q(16)+**log**_q(q/2) = p +**log**_q(q)-**log**_2(2)=p+1-**log**_q(2)**log**_q(2) = 1/4log_q(16) since 2^4=16 so**log**_q(8q)=3/4p+13 Answers · Science & Mathematics · 12/11/2008

**log**[(x+4)/(x-2)] -**log**3 = 0 (now divide what's inside the first**log**by 3, it's one of the laws)**log**[(x+4)/(x-2) * (1/3)] = 0**log**[(x+4)/(3x-6)] = 0 (one of the laws: the base of the**log**to the...2 Answers · Science & Mathematics · 19/02/2011

**log**_(1/a) (b) =**log**_a(b) /**log**_a(1/a) =**log**_a(b)/**log**_a (a^(-1) =**log**_a(b)/(-1) = -**log**_a(b) so f(**log**_a(x)) =**log**_a(x) * (-**log**_a(x)) ==> f(**log**_a(x)) = -(**log**_a(x))^2 ==> f(x) = -x^22 Answers · Science & Mathematics · 05/12/2016

**log**(x + 11) -**log**(x) = 3 Using**log**rules, we can combine the logs into...11) / x) = 3 Raise 10 to the power of each side to eliminate the**log**: (x + 11) / x = 1000 Multiply each side by x: x + 11 = 1000x...4 Answers · Science & Mathematics · 28/03/2012